Extracellular vesicles in cancer ́s communication: messages we can read and how to answer - Semeradtova, Alena; Liegertová, Michaela; Herma, Regina; Capkova, Magdalena; Brignole, Chiara; Del Zotto, Genny (Molecular cancer, 2025)
Extracellular vesicles (EVs) are emerging as critical mediators of intercellular communication in the tumor microenvironment (TME), profoundly influencing cancer progression. These nano-sized vesicles, released by both tumor and stromal cells, carry a diverse cargo of proteins, nucleic acids, and lipids, reflecting the dynamic cellular landscape and mediating intricate interactions between cells. This review provides a comprehensive overview of the biogenesis, composition, and functional roles of EVs in cancer, highlighting their significance in both basic research and clinical applications. We discuss how cancer cells manipulate EV biogenesis pathways to produce vesicles enriched with pro-tumorigenic molecules, explore the specific contributions of EVs to key hallmarks of cancer, such as angiogenesis, metastasis, and immune evasion, emphasizing their role in shaping TME and driving therapeutic resistance. Concurrently, we submit recent knowledge on how the cargo of EVs can serve as a valuable source of biomarkers for minimally invasive liquid biopsies, and its therapeutic potential, particularly as targeted drug delivery vehicles and immunomodulatory agents, showcasing their promise for enhancing the efficacy and safety of cancer treatments. By deciphering the intricate messages carried by EVs, we can gain a deeper understanding of cancer biology and develop more effective strategies for early detection, targeted therapy, and immunotherapy, paving the way for a new era of personalized and precise cancer medicine with the potential to significantly improve patient outcomes.
Keywords: nádorové biomarkery; extracelulární vezikuly; Neoplasms; Biomarkers, Tumor; Tumor Microenvironment; zvířata; Extracellular Vesicles; nádorové mikroprostředí; lidé; nádory; Humans; Cell Communication; mezibuněčná komunikace; Animals